BUDAYA ONDEL-ONDEL: PERGESERAN MAKNA, FENOMENA NGAMEN, DAN IMPLIKASI TERHADAP IDENTITAS ETNIS MASYARAKAT BETAWI - Tatang Yusup; M. Arifin Ritani Noor (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
In the Betawi cultural tradition, ondel-ondel has long been considered an icon and is also believed to be a repellent in traditional rituals. However, now is the ondel-ondel ngamen phenomenon that has caught the public's attention. This study employed a descriptive qualitative method with a phenomenological approach. Data were collected through nonparticipant observation, in-depth interviews, literature studies, and online data searches. The results showed that the Betawi ondel-ondel art underwent a significant change in meaning from magical and ritualistic aspects to becoming a medium of entertainment to advance the city of Jakarta as a tourist destination. This change has occurred since 1966, when ondel-ondel was modified into a large doll with a friendly face and various clothes, increasing its attractiveness to visitors. This transformation includes removing the scary impression by no longer using canine teeth, replacing ondel-ondel wasp music with Betawi songs without incantations or offerings, and changing ondel-ondel's movements to become more regular and by the rhythm of the song. However, even though ondel-ondel has turned into a more popular medium of entertainment by taking to the streets to busk as a source of income, the current state of ondel-ondel art is not in harmony with its function as an entertainment medium. Its appearance is simple and does not comply with standard regulations, making ondel-ondel art less attractive, thus changing the function of entertainment into an economic function. The mistake of using ondel-ondel for busking has caused concern and resentment among the Betawi people. Many of them consider ondel-ondel as part of Betawi culture, icons and arts that should be preserved and appreciated. The use of ondel-ondel for busking is considered to reduce the meaning and artistic value. Most Betawi people do not support the use of ondel-ondel as a busking tool and tend not to give money to ondel-ondel singers.